Organocatalytic asymmetric cascade reaction of gamma-substituted deconjugated butenolides with o-formyl-beta-nitrostyrene - Deepake, Siddharth K.; Lanjewar, Atul B.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2018)
An efficient chemo-, diastereo- and enantio-selective cascade synthesis of functionalized indanols bearing four contiguous stereogenic centres has been developed via the reaction of beta,gamma-butenolides with o-formyl-beta-nitrostyrenes in the presence of bi-functional hydrogen-bonding catalyst. Indanol derivatives containing gamma,gamma-disubstituted butenolides were obtained in good yields and with moderate to high enantioselectivities/diastereoselectivities.
Keywords: butenolides; Cascade reaction; Enantioselectivity; Indanol; organocatalysis

1,6-Conjugate-addition-induced [2+1] annulation of para-quinone methides and pyrazolones: synthesis of bis-spiro compounds with contiguous quaternary spiro-centers - Kale, Someshwar B.; Jori, Popat K.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (Organic Letters, 2019)
A diastereoselective formal 1,6-conjugate-addition-mediated [2 + 1] annulation reaction using p-quinone methides and pyrazolones has been described. The corresponding bis-spiro[cyclohexadienone-cyclopropane-pyrazolone] compounds were obtained in very good yield under mild reaction conditions.

Alpha-Angelica lactone in a new role: facile access to N-Aryl tetrahydroisoquinolinones and isoindolinones via organocatalytic alpha-CH2 oxygenation - Thatikonda, Thanusha; Deepake, Siddharth K.; Das, Utpal (Organic Letters, 2019)
A method for the direct oxidation of various N-aryl tetrahydroisoquinolines and isoindolines to the corresponding lactams using alpha-angelica lactone as a catalyst was developed. The utility of the method was further demonstrated by synthesis of indoprofen and indobufen.

Alpha-Angelica lactone catalyzed oxidation of benzylic sp(3) C-H bonds of isochromans and phthalans - Thatikonda, Thanusha; Deepake, Siddharth K.; Kumar, Pawan; Das, Utpal (Organic & Biomolecular Chemistry, 2020)
A metal-free organocatalytic system has been developed for highly efficient benzylic C-H oxygenations of cyclic ethers using oxygen as an oxidant. This oxidation reaction utilizes alpha-angelica lactone as a low cost/low molecular weight catalyst. The optimized reaction conditions allow the synthesis of valued isocoumarins and phthalides from readily available precursors in good yields. Mechanistic studies indicate that the reaction pathway likely involves a radical process via a peroxide intermediate.

Functionalization of alkynes and alkenes using a cascade reaction approach: synthesis of beta-keto sulfones under metal-free conditions - Kumar, Mukesh; Ahmed, Riyaz; Singh, Maninder; Sharma, Shweta; Thatikonda, Thanusha; Singh, Parvinder Pal (Journal of Organic Chemistry, 2020)
Here, we are reporting a multicomponent cascade reaction approach for the synthesis of beta-keto sulfones by exploiting differential reactivity pattern of substrates under open-atmosphere and metal-free conditions. The coupling partners are aryldiazonium salts, unsaturated compounds, and DABSO. The optimized conditions worked well with both alkenes and alkynes. Moreover, the reaction also works with metabisulfite for the source of sulfone. The controlled liquid chromatography-mass spectrometry and O-18-labelled experiments suggested that air is a source of the incoming oxygen atom of the keto group of beta-keto sulfones.